Mengungkap Makna Memutus Perselisihan Hasil Pemilihan Umum Presiden dan Wakil Presiden Indonesia dalam Putusan Mahkamah Konstitusi - Nadir, Nadir; Wardani, Win Yuli; Wahyono, Sapto (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to reveal the meaning of resolving disputes over the results of the Indonesian Presidential and Vice Presidential elections. The research method used is doctrinal research. This type of research is research on laws that are conceptualized and developed based on the doctrine adopted by the conceptualizer and/or developer using data from primary and secondary legal materials and data analysis using theoretical and interpretation instruments. The results of this study indicate that the essence of the judge's decision is the end of a series of trials and is the final responsibility of a judge for the case being examined and tried and a reflection of the values ​​of justice, truth, certainty, benefit, ethics, and morals of the judge concerned. In addition, the judge's decision is a statement of the judge's will as the owner of the authority pronounced in a closed or open trial for the public and aims to end a case. Therefore, without a judge's decision, the case will not end, especially in disputes over the presidential and vice presidential elections in order to achieve justice, certainty and benefit, although all three are not necessarily achieved. In addition, the legal implications of the Constitutional Court's decision in deciding the results of the Presidential and Vice Presidential elections, namely in the 2024 Presidential and Vice Presidential Election dispute, the Constitutional Court's decision determines the law and does not create a new legal situation because it does not change the KPU's decision and the applicant's application is rejected in its entirety, and the Constitutional Court's decision implies the implementation of the authority of the People's Consultative Assembly to inaugurate the President and/or Vice President as stipulated in Article 3 paragraph (2) of the 1945 Constitution of the Republic of Indonesia.